Perencanaan Partisipatif Dalam Proses Pemberdayaan Masyarakat : (Studi Kasus Program Nasional Pemberdayaan Masyarakat Mandiri Perdesan Di Kecamatan Trowulan Kab. Mojokerto) - Bambang Agoes Hermanto (FT- UNDAR, 2014)
Development planning in the era Suharto (orba) emphasis on Top Down approach and the result of high growth in the economic growth but poverty levels are still high. The new era (reformasi), there is a new approach of national planning that is Bottom Up which involves sociaty to participate on the development planning by issuing law number 25, 2004. This lwa has been applied since 2004. The result is the same as on era Suharto (orba) that is high growth in the economic growth but poverty levels are still high. On the low level of development planning such as in the case of UPK PNPM MD Trowulan districts. PNPM MD Trowulan district has been applied development planning which involves community to participate on the planning but the result of such programs are still weak. The comunity has poor data to get a good program so that very often their proposals are omitted. So that they feel useless to participate on he program. Therefore, they less participate in the end of the programe. Pendahuluan